2020
DOI: 10.1109/access.2020.2996282
|View full text |Cite
|
Sign up to set email alerts
|

Deep Tensor Capsule Network

Abstract: Capsule network is a promising model in computer vision. It has achieved excellent results on simple datasets such as MNIST, but the performance deteriorates as data becomes complicated. In order to address this issue, we propose a deep capsule network in this paper. To deepen the capsule network, we present a new tensor capsule based routing algorithm and the corresponding convolution operation. Compared to vector capsules, tensor capsules can capture more instance-level information. Together, the relevant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Each neuron of a capsule encodes spatial information, while the vector's length encodes the probability of the entity being present. While the first architecture proposed in [4] is composed of only three layers, recently deeper CapsNet models were proposed [13] [32]. The main components of a CapsNet are the following:…”
Section: B Convolutional and Capsule Network Hardwarementioning
confidence: 99%
“…Each neuron of a capsule encodes spatial information, while the vector's length encodes the probability of the entity being present. While the first architecture proposed in [4] is composed of only three layers, recently deeper CapsNet models were proposed [13] [32]. The main components of a CapsNet are the following:…”
Section: B Convolutional and Capsule Network Hardwarementioning
confidence: 99%
“…Capsule networks suffer from expensive computational methods, yet numerous routing layers increase training costs and inference time because of the complexity of the network [29]. Researchers in [24] have, on the other hand, demonstrated that the prediction time is significantly shorter than that of other deep learning techniques.…”
Section: Cnn Is Currently Used In Many Applications and Has Shown Sat...mentioning
confidence: 99%
“…As shown in [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], the network structure defines a discrete n -dimensional geometric space. In the introduced space for each individually selected packet flow, for which the conditions of QoS assurance will be obtained, the network will be described by a mixed bivalent tensor [ 19 , 20 , 21 ]: where is the tensor multiplication operator;…”
Section: Tensor Description Of the Network And Formalization Of Quality Of Service Assurance Conditionsmentioning
confidence: 99%
“…Due to the direct analogy of electrical and communication network processes, the tensor analysis apparatus applies to a wide range of traffic management and routing [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, in terms of their structural and functional construction, communication networks are more complex systems than electrical circuits.…”
Section: Introductionmentioning
confidence: 99%